Islamic Ethics and the Future of Digital Diplomacy: Lessons from China’s Digital Silk Road - Novi Rizka Amalia; Sartika Soesilowati; Siti Rochmawati Soesanto (Dauliyah Journal of Islamic and International Affairs, 2026)
The evolution of global diplomacy into the digital sphere presents both unprecedented opportunities and profound ethical challenges. China's Digital Silk Road (DSR), as part of its broader Belt and Road Initiative, has become a significant instrument of soft power projection, particularly in the Muslim-majority regions of Southeast Asia. While the DSR emphasises connectivity and technological advancement, it also raises questions related to justice, sovereignty, surveillance, and digital control. This paper seeks to examine these developments through the lens of Islamic ethics, emphasising principles such as adl (justice), shura (consultation), karamah al-insaniyyah (human dignity), and amanah (trust). By critically engaging with China's digital diplomacy strategy, this study argues that Islamic ethical thought offers a robust normative framework capable of guiding more just, transparent, and humane approaches to digital international engagement. In doing so, the paper contributes to the development of an Islamic discourse on digital diplomacy, positioning Islamic ethics as a vital foundation for shaping the future of the global digital order.